PERLINDUNGAN HUKUM TERHADAP PRODUK INDIKASI GEOGRAFIS KOPI ARABIKA JAVA SINDORO-SUMBING - M. Rangga Yusuf; Hernawan Hadi (Program Pascasarjana Fakultas Hukum Universitas Sebelas Maret Surakarta, 2019)
AbstractThis article aims to examine the legal issues and to find out the the law enforcement of Geographical Indication dispute settlement. The method for this research is empirical law research (sociology/non-doctrinal). The descriptive research category and object of this research in Farmers Group of Bina Sejahtera and Association of Geographical Indication Protector of Kopi Arabika Java Sindoro-Sumbing is analyzed by interviewing the law effectiveness action and also using qualitative analysis approach. The result of this research shows that the law protection for Kopi Arabika Java Sindoro-Sumbing’s Geographical Indication has given the right and protection for it. Based on juridical aspect it has been regulated in Law Number 20 of 2016 about trademark and Geographical Indication Jo. Government Regulation Number 51 of 2007 about Geographical Indication. Yet in the practical fact those laws have not work as they should be. Due to many violations of the using of Geographical Indication right and also the violation cases settlement that hasn’t been continued. So that, the law enforcement is needed to solve the settlement on Geographical Indication violations, either with litigation or non-litigation.Key Words: Law Protection; Geographical Indication; Kopi Arabika Java Sindoro-Sumbing.AbstrakArtikel ini bertujuan mengkaji isu hukum dan untuk mengetahui upaya hukum penyelesaian sengketa dibidang Indikasi Geografis. Metode penelitian yang digunakan adalah penelitian hukum empiris (sosiologis/ non doktrinal). Sifat penelitian deskriptif dan obyek penelitian di Kelompok Tani Kopi Bina Sejahtera dan Masyarakat Pelindung Indikasi Geografis Kopi Arabika Java Sindor-Sumbing dilakukan dengan wawancara terhadap efektivitas hukum dan pendekatananalisis kualitatif. Hasil penelitian ini diketahui bahwa bentuk perlindungan hukum Indikasi Geografis Kopi Arabika Java Sindoro-Sumbing secara yuridis telah diatur melalui UndangUndang Nomor 20 Tahun 2016 tentang Merek dan Indikasi Geografis Jo. Peraturan Pemerintah Nomor 51 Tahun 2007 tentang Indikasi Geografis. namun dalam prakteknya perlindungan tidak berjalan sebagaimana mestinya. Karna masih terjadinya bentuk pelanggaran penggunaan tanpa hak tanda Indikasi Geografis dan masih terdapat kasus pelanggaran yang belum ditindaklanjuti dalam penyelesaiaanya. Sehingga diperlukan upaya hukum untuk menyelesaikan sengketa atas pelanggaran Indikasi Geografis baik secara non litigasi dan litigasi.Kata Kunci: Perlindungan hukum; Indikasi Geografis; Kopi Arabika Java Sindoro-Sumbing.